Mesenteric inflammatory veno-occlusive disease: what is it and why it is important to know it? - Zia Ur Rehman (Journal of the Pakistan Medical Association, 2022)
Madam, Mesenteric inflammatory veno-occlusive disease (MIVOD) is an unusual cause of mesenteric venous thrombosis. It is localized inflammation of the mesenteric veins and venules. The adjacent arteries are normal and spared from the inflammatory process. There is no evidence of systemic vasculitis or any other local bowel pathology. This focal inflammatory process leads to bowel ischaemia and necrosis. It is histopathological diagnosis showing lymphocytic infiltration of bowel wall, chronic inflammation in the mesenteric veins. There are also features intraluminal thrombosis and features of bowel ischaemia. It is important to know this condition as its treatment is different from other causes of mesenteric venous thrombosis. Continuous...